The Relationship Between Nutritional Status and Nutritional Intake Towards Intelligence Level (IQ) - Kamilah Ramadhani Arif; Syamsu Rijal; Marzelina Karim; Asrini Safitri; Sidrah Darma (Journal La Medihealtico, 2026)
Nutritional status plays an important role in children's growth and development, including cognitive development and intelligence. School-aged children are a vulnerable group to nutritional problems that may affect learning ability. An observational analytic study with a cross-sectional design was conducted among 36 students aged 11–12 years. Nutritional status was assessed using Body Mass Index-for-Age (BMI-for-age) based on CDC standards, nutrient intake was measured using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and intelligence was measured using the Wechsler Intelligence Scale for Children (WISC). Data analysis was performed using univariate, bivariate (One Way ANOVA), and multivariate (linear regression) analyses. Most respondents had normal nutritional status and average IQ scores. There was no significant relationship between nutritional status and IQ (p = 0.095). Multivariate analysis also showed no significant effect of nutritional status and nutrient intake on IQ (p = 0.797; R² = 0.072). Nutritional status and nutrient intake were not significantly associated with intelligence levels among school-aged children in this study.